PROFITABILITY MEDIATES THE EFFECT OF INVESTMENT DECISIONS ON COMPANY OF VALUE - Santoso, Aprih (Media Mahardhika, 2020)
The objectives of this study are: analyze and empirically test the effect of investment decisions on the profitability of going public insurance companies listed on the Indonesia Stock Exchange in 2013-2018; analyze and empirically test the effect of investment decisions on the value of go public insurance companies listed on the Indonesia Stock Exchange in 2013-2018 and analyze and test empirically the effect of profitability on the value of go public insurance companies listed on the Indonesia Stock Exchange in 2013-2018. The type of data used is secondary data in the form of annual financial statements of listed companies listed on the Indonesia Stock Exchange. The population of this research is publicly listed insurance companies listed on the Indonesia Stock Exchange in 2013-2018. The sampling technique was carried out using purposive sampling, the sample of which went public insurance companies listed on the Indonesia Stock Exchange in 2013-2018 totaling 60 issuers. Data analysis techniques used are descriptive statistical tests, classic assumption tests, multiple linear regression tests, mediation variable tests and model feasibility tests. Based on the results of research testing concluded that: (1) Investment decisions have a negative and significant effect on profitability. (2) Investment decisions have a positive and significant effect on company value. (3) Profitability has a positive and significant effect on firm value. (4) Profitability cannot mediate between investment decisions and firm value. Variation of investment and profitability decision variables used in this model is able to explain variations in the variable value of companies going public insurance listed on the Indonesia Stock Exchange 2013-2018 64%, while the rest is influenced or explained by other variables not included in this research model.